Awareness, efficacy, and readiness on the usability of counseling service application software to enhance the academic outcome - Abdulmutalib Opeyemi Adio; Hameed Olamilekan Bolaji (Universitas Pendidikan Indonesia, 2024)
With the emergence of e-counseling applications, counseling services can now be provided to clients online. This study examines secondary school counselors' awareness, efficacy, and readiness to utilize counseling service application software in Lagos, Nigeria. Using a descriptive survey design, data were collected through a standardized questionnaire validated by experts. The analysis revealed that counselors exhibit low awareness, capability, and readiness to use such software. Additionally, there is a moderate positive relationship between these variables and the usability of counseling applications, which is statistically significant. These findings highlight the need for training programs to enhance counselors’ awareness and competencies. Support from the government and educational institutions is essential to promote the adoption of this technology, which can improve counseling effectiveness, support students’ mental health, and enhance academic outcomes. Collaboration with technology experts is strongly recommended to optimize the application of this software in counseling practices. Abstrak Munculnya aplikasi e-konseling, layanan konseling kini dapat diberikan kepada klien secara online. Penelitian ini mengkaji tingkat kesadaran, efikasi, dan kesiapan konselor sekolah menengah di Lagos, Nigeria, dalam menggunakan perangkat lunak aplikasi layanan konseling. Dengan desain survei deskriptif, data dikumpulkan melalui kuesioner terstandar yang telah divalidasi oleh para ahli. Analisis data menunjukkan bahwa konselor memiliki tingkat kesadaran, kemampuan, dan kesiapan yang rendah terhadap penggunaan perangkat lunak tersebut. Hasil juga menunjukkan adanya hubungan positif yang moderat antara ketiga variabel tersebut dengan kegunaan aplikasi konseling, yang signifikan secara statistik. Temuan ini menyoroti pentingnya program pelatihan yang dirancang untuk meningkatkan kesadaran dan kompetensi konselor. Dukungan pemerintah dan institusi pendidikan diperlukan untuk memfasilitasi adopsi teknologi ini, yang diharapkan dapat meningkatkan efektivitas layanan konseling, mendukung kesehatan mental siswa, serta memperbaiki hasil akademik mereka. Kolaborasi dengan pakar teknologi sangat dianjurkan untuk memaksimalkan penerapan perangkat lunak ini dalam praktik konseling. Kata Kunci: aplikasi layanan konseling; konseling; teknologi